Pliocene clastic sediments in Western Goričko, Northeastern Slovenia - Kralj, Polona (Geologija, 2001)
Upper Pliocene clastic sediments from Goričko have been deposited in fluvial environments. The oldest are alluvial fan and braided river deposits, composed of gravelly sands and sandy gravels. Imbrications indicate the transport directions from northwest to southeast. The following sedimentation was dominated by a meandering river. Sands and flood basin fine-grained sediments infilled the existing paleorelief, produced by alluvial fan, braided river and volcanic deposits.